Monetary compensation schemes during the COVID-19 pandemic: Implications for household incomes, liquidity constraints and consumption across the EU - Michael Christl; Silvia De Poli; Francesco Figari; Tine Hufkens; Chrysa Leventi; Andrea Papini; Alberto Tumino (Global Labor Organization (GLO), 2022)
This paper analyses the effect of the COVID-19 pandemic on household disposable income and household demand in the European Union (EU), making use of the EU microsimulation model EUROMOD and nowcasting techniques. We show evidence of heterogeneity in the impact of the COVID-19 pandemic on the labour markets in EU Member States, with some countries hit substantially harder than others. Most EU Member States experience a large drop in market incomes in 2020, with poorer households hit the hardest. Tax-benefit systems cushioned significantly the transmission of the shock to the disposable income and the household demand, with monetary compensation schemes playing a major role. Additionally, we show that monetary compensation schemes prevent a significant share of households from becoming liquidity constrained during the pandemic.
Keywords: 330; COVID-19; Inequality; Microsimulation; EUROMOD